The Influence Of Digital Culture And Digital Leadership On Innovation Capabilities With Digital Capabilities As A Mediation Variable - Oey Hannes Widjaja; Lianah The; Marcello Marcello; Dova Dova (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are productive business activities owned by individuals or business entities that meet certain criteria based on the amount of assets and annual turnover. MSMEs play a strategic role in the Indonesian economy because they absorb a large portion of the workforce and are the backbone of economic activity. This study aims to analyze the effect of digital culture, digital leadership, and innovation capabilities, with capabilities as a mediating variable. The sample size for this study was 200 respondents who were MSME actors. The method used was purposive sampling by distributing questionnaires online and offline. Data were analyzed using the SEM-PLS model through SmartPLS 4 software.